2005
DOI: 10.1074/jbc.m502736200
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Export Factor Family Protein Participates in Cytoplasmic mRNA Trafficking

Abstract: In eukaryotes, the nuclear export of mRNA is mediated by nuclear export factor 1 (NXF1) receptors. Metazoans encode additional NXF1-related proteins of unknown function, which share homology and domain organization with NXF1. Some mammalian NXF1-related genes are expressed preferentially in the brain and are thought to participate in neuronal mRNA metabolism. To address the roles of NXF1-related factors, we studied the two mouse NXF1 homologues, mNXF2 and mNXF7. In neuronal cells, mNXF2, but not mNXF7, exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
62
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 69 publications
1
62
0
Order By: Relevance
“…Nevertheless, a preferential inactivation (480%) of one of the X-chromosomes was found in the mothers of Cases 1, 7, and 8 (Table 1; column ''Xinactivation'') and provides additional evidence for causality, which was confirmed for the MECP2 duplication in Case 7 [Van Esch et al, 2005a]. Case 8 harbors a 0.8-Mb duplication at Xp22 including the candidate MR gene NXF5 implicated in mRNA transport in dendrites [Jun et al, 2001], and later confirmed for the mouse homolog Nxf7 [Tretyakova et al, 2005]. Therefore, increased dosage of NXF5 might disturb storage levels of particular mRNAs in neurons.…”
Section: Discussionmentioning
confidence: 82%
“…Nevertheless, a preferential inactivation (480%) of one of the X-chromosomes was found in the mothers of Cases 1, 7, and 8 (Table 1; column ''Xinactivation'') and provides additional evidence for causality, which was confirmed for the MECP2 duplication in Case 7 [Van Esch et al, 2005a]. Case 8 harbors a 0.8-Mb duplication at Xp22 including the candidate MR gene NXF5 implicated in mRNA transport in dendrites [Jun et al, 2001], and later confirmed for the mouse homolog Nxf7 [Tretyakova et al, 2005]. Therefore, increased dosage of NXF5 might disturb storage levels of particular mRNAs in neurons.…”
Section: Discussionmentioning
confidence: 82%
“…It is known that NXF1 proteins function as a part of macromolecular complexes and interact with different factors (Kataoka et al 2000;Stutz et al 2000;Le Hir et al 2001;Rodrigues et al 2001;Gatfield and Izaurralde 2002;Blevins et al 2003;Huang et al 2003;Forler et al 2004;Ooe et al 2004;Tretyakova et al 2005). Such interactions have been demonstrated for orthologues of Dm NXF1 in humans (Hs NXF1/TAP) and mice (Mm NXF1).…”
Section: Discussionmentioning
confidence: 94%
“…The genes of this family are involved in controlling the transport of mRNA Herold et al 2001;Jun et al 2001;Sasaki et al 2005;Tretyakova et al 2005). The sbr or Dm nxf1 gene of Drosophila melanogaster encodes the main transport receptor of mRNA and is orthologous to the Tap/Hs nxf1 gene of humans and the Mm nxf1 gene of mice (Herold et al , 2003Sasaki et al 2005;Tretyakova et al 2001).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although most studies of Mtap1b-LC1 have centered on its interaction with microtubules, several roles have been proposed for microtubule-associated proteins in processes that may be independent of microtubule function. For example, in neuroblastoma cells Tau-1 has been identified in the fibrillar component of nucleoli as well as in the nucleolar organizer regions, both places where ribosome biogenesis is initiated (40), and Mtap1b-LC1 has been shown to interact with proteins involved in diverse processes such as mRNA trafficking and cAMP signaling (47,48). It is, therefore, plausible that the inter-action of Pes1 with Mtap1b-LC1 is unrelated to the binding of Mtabp1b-LC1 to microtubules and could reflect an as-yet unidentified role for Mtap1b-LC1 in controlling ribosome formation.…”
Section: Discussionmentioning
confidence: 99%